The potential benefit of omega-3 fatty acid capsule on Mean platelet volume and Platelet count in type-2 Diabetes Mellitu - Habib, Tamanna Binte; Akhter, Qazi Shamima; Imam, Hasan; Yeasmin, Nahid; Nahar, Sharmin; Rahman, Farhana (Bangladesh Critical Care Journal, 2020)
Background: Diabetes Mellitus (DM) is a major non-communicable health problem that has effects on glycemic status. Hyperglycemia that is an inherent finding of diabetes causes platelet dysfunction. Oral omega-3 fatty acid supplementation may improve glycemic status in diabetic patient and reduce micro and macrovascular complications. Objective: To observe the effect of supplementation of omega-3 fatty acid on Mean Platelet Volume (MPV) and Platelet count in type 2 DM. Methods: A prospective interventional study was conducted from January 2017 to December 2017. A total numbers of 52 diagnosed type 2 diabetic patients of both sexes were selected within age 40 to 50 years. Among them, 27 type 2 diabetic patients with supplementation of omega 3 fatty acid (2g/day) for 12 weeks were considered as study group and another 25 type 2 diabetic patients without supplementation of omega 3 fatty acid were considered as control group. The study subjects were selected from Outpatient Department of Endocrinology, Dhaka Medical College Hospital, Dhaka and personal contact from Dhaka city. MPV and platelet count were measured by hematology analyzer. The study parameters were measured at base line and after 12 weeks of study period in both groups. Results: In this study MPV and platelet count levels were significantly lower (p<.001) in diabetic patients after supplementation with omega-3 fatty acid in comparison to that of their baseline value. Again, after 12 weeks, MPV and platelet count were significantly lower (p<.001) in diabetic patients after supplementation with omega-3 fatty acid in comparison to control group. In control group, MPV and Platelet count were almost similar both at baseline and after 3 months of follow-up. Conclusion: After analyzing the results of the study it can be concluded that omega-3 fatty acid may improve MPV and Platelet count levels in type 2 diabetic patients and may be helpful to minimize the complications of type-2 DM. Bangladesh Crit Care J March 2020; 8(1): 37-40